Romeo and Juliet from page to screen: A multilateral model for the analysis of three Italian films. (8th May 2012) - Minutella, Vincenza
The article examines three Italian film adaptations of Shakespeare's Romeo and Juliet, directed by Castellani (1954), Freda (1964) and Torre (2000). As the tragedy of the lovers was originally an Italian tale that reached Shakespeare through translation and rewriting, this article explores the journey of the story back to Italy through a process of translation into a different medium, interpretation and re-appropriation by Italian directors. The transposition from page to screen is seen as a process of translation and is analysed adopting the 'star-like' model suggested by Cattryss, which looks for the models or semiotic devices that have affected the production of a film. The article analyses the interpretations given by the Italian directors and identifies the different 'source texts' that might have influenced the translation from page to screen.